(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Quay gantry type calculates in the technical literature in the form of a frame with hard rigel and rigid stopping up of piles. To account for long-term durability of the structures in the plastic clay soils in the existing scheme is additionally used the equation of state of a Newtonian viscous fluid. In Its uses the coefficient of shear viscosity.The author used the proposed of the early engineering universal method of calculating berthing quays with respect to the thin walls, secured of anchor piles. In the design scheme not used lower secured racks, and counts up the stiffness characteristics of the soil, clarifying the nature of the work structures.To account for the operation of facilities in the plastic clay soils in the proposed scheme uses a different equation of state of a Newtonian viscous fluid. It uses the ratio of the coefficient of viscosity in compression of porous soil (coefficient of Trutona).This allows us to consider how long-term strength and displacement of the structure in time.Considers the issues of contamination and turbidity in the reconstruction of the gantry bulwark.